Development of a Scale to Measure Memorable Tourism Experiences - Kim, Jong-Hyeong; Ritchie, J.R.; McCormick, B. (SAGE Publications Inc, 2012)
The quality experiences provided to customers, which are indeed memorable, directly determine a business’s ability to generate revenue (Pine and Gilmore 1999). However, the extant tourism literature has provided limited explanation of the factors that characterize memorable tourism experiences. Thus, the goal of the present study was to develop a valid and reliable measurement scale that will assist in understanding the concept and in improving the effective management of the memorable experience. Following Churchill’s (1979) recommended process, we developed a 24-item memorable tourism experience scale that we believe is applicable to most destination areas. The scale comprises seven domains: hedonism, refreshment, local culture, meaningfulness, knowledge, involvement, and novelty. The data support this dimensional structure of the memorable tourism experience as well as its internal consistency and validity (i.e., content, construct, convergent, and discriminant validity). Theoretical and managerial implications of the study results are discussed in detail.